Analisis Peran Literasi Digital Masyarakat dalam Menyikapi Isu Kejahatan Digital pada Penyebaran Cyberbullying di Media Sosial - Arin Nurhidayah; Nurmala Dwi Winata; Ratu Syiva Ullaya; Rifki Dwi Naufal; Tatu Neli Nurfarihah; Ali Alfauzi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Advances in information and communication technologies have increased the use of social media platforms as a tool for interacting and sharing information. However, this convenience has also been accompanied by the emergence of various types of cybercrime, including cyberbullying. The low level of digital understanding among people can affect the ability of individuals to understand the ethics of media use, assess information wisely and be aware of the consequences of actions taken in the digital space. As a result, cyberbullying is still common and can cause various psychological effects for victims, such as stress, anxiety, decreased self-esteem to mental health issues. This study aims to analyze the role of people's digital understanding in dealing with cybercrime problem that is cyberbullying on social media platforms. The method applied is the Systematic Literature Review (SLR) by examining a wide range of relevant scientific literature. The findings of the analysis suggest that digital literacy has a significant role to play in shaping society's more thoughtful, critical and responsible behaviour towards social media use. Digital literacy also contributes to the community in recognizing forms of cyberbullying, preventing participation in such behaviors and providing appropriate responses. Therefore, increasing digital literacy through education and socialization needs to be continuously implemented in order to create a safer digital environment and reduce the spread of cyberbullying.